Kesejahteraan Dalam Perspektif Islam Pada Karyawan Bank Syariah - Ziauddin Sardar; Muhammad Nafik H.R (Universitas Airlangga, 2016)
Muslims required to work through legal means, but as human beings sometimes lust to dominate oneself so a man would prefer to work in a place that is run in activities contrary to the rules of Islam simply because the payment is obtained at the site is greater. The purpose of this research was to determine how the financial and non-financial welfare of employees and the Islamic banks to determine the reasons employees relocate to Islamic banks. For the informants who have the motivation to move because of a reason to avoid usury laws, could be said to be better in terms of non-financial welfare. For the informant who aim to move into Islamic banks due to other reasons, in terms of the welfare of both financial and nonfinancial could be said to be prosperous just not better than the employees who move for some reason wants to avoid usury.